Pengaruh Persepsi Risiko dan Kepercayaan (Trust) pada Adopsi Layanan Fintech (Studi Kasus pada Layanan Pembayaran Digital Gopay) - Eni Wijaya; Riauli Susilawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
GoPay is the most popular digital payment in Indonesia. However, the increasing number of risks posed by GoPay adds to people's concerns in using GoPay. Even so, there are still some people who believe and continue to use it. Therefore, this study was conducted with the aim to determine whether there is an influence of perceived risk and trust in the use of GoPay services by using one of the constructs of the Technology Accepted Model (TAM), Actual Use. This study uses a quantitative approach. The data analysis technique used in this study is descriptive analysis and multiple linear regression. The results show that simultaneously perceived risk and trust affects the actual use of GoPay in Bandung. Partially, the perceived risk has a negative and significant effect on the actual use of GoPay. Meanwhile, trust has a positive and significant effect on the actual use of GoPay.